Experiences and Perspectives From Women Taking Investigational Therapy for Hepatitis C Virus During Pregnancy - Yasaswi Kislovskiy; Catherine Chappell; Emily Flaherty; Megan E Hamm; Flor de Abril Cameron; Elizabeth E Krans; Judy C Chang (SAGE Publishing, 2021)
Objective: Describe the experiences and perspectives among pregnant people with chronic HCV infection receiving ledipasvir/sofosbuvir (LDV/SOF) therapy during pregnancy. Methods: We conducted semi-structured, in-depth interviews within an open-label, phase 1 study of LDV/SOF therapy among pregnant people with chronic HCV infection. Participants took 12 weeks of LDV/SOF and were interviewed at enrollment and again at the end of treatment. We transcribed the interviews verbatim and coded them with NVivo software for subsequent inductive thematic analysis. Results: Nine pregnant people completed the study, leading to 18 interview transcripts. All participants identified as women. Eight women acquired HCV through injection drug use, and 1 through perinatal transmission. We identified 3 themes. (1) Treatment for HCV during pregnancy with LDV/SOF was tolerable and convenient. (2) Women described that taking investigational LDV/SOF increased their self-esteem and sense of well-being due to possible cure from HCV, and they felt that the experience of working hard to achieve cure may potentially prevent return to drug abuse in the future. (3) Women appreciated researchers and providers that gave non-judgmental care and communicated honestly, and preferred person-centered care that acknowledges women's individual needs. Conclusions: Women stated that cure from HCV would be "life-changing," and described antepartum treatment for HCV with LDV/SOF as tolerable and desired, when provided by non-judgmental providers. Antepartum treatment was found to be acceptable by study participants and should be further evaluated to combat the increasing HCV epidemic among young persons, including pregnant people.